Valuations of early-stage companies and disruptive technologies : how to value life science, cybersecurity and ICT start-ups, and their technologies - Rothman, Tiran (Palgrave Macmillan, 2020)
This book will serve as a practical guide for entrepreneurs and investors/advisors in constructing and understanding valuations of startups in rapidly shifting industries, including the areas of drug development, medical devices, cyber security, and renewable energy. For large companies, valuation is based on forecasts of free cash flow; in technologically-driven industries, product pipelines can represent a large part of market capitalization. The situation is even more critical for small companies committed to a single idea: all of their value is linked to a single project. Any business transaction or internal proposal to begin or terminate an R&D project in which innovative projects are being valued or exchanged requires a realistic valuation of those projects. Moreover, different projects have very different dynamics. Pharmaceuticals have very large lead times and are dependent on patents as well as out-licensing agreements. In contrast, software develops very quickly, and IP is hard to value. This book will be a guide to building appropriate valuations for companies competing in rapidly shifting industries and offering products under new business models where little precedent exists, taking both financial and behavioral issues into consideration.